(untitled) - Rushbrook, Philip (Washington, D.C, 1999)
This books consists of the following many parts such as wate characteristics, landfill site identification, site design and preparation, landfill site operation, additional provision for difficult wastes.
Keywords: Refuse and refuse disposal,Sanitary landfills; Developing countries,Design and construction